2021
DOI: 10.1002/epi4.12535
|View full text |Cite
|
Sign up to set email alerts
|

sEEG for expansion of a surgical epilepsy program: Safety and efficacy in 152 consecutive cases

Abstract: Objective: Stereoelectroencephalography (sEEG) is an intracranial encephalography method of expanding use. The need for increased epilepsy surgery access has led to the consideration of sEEG adoption by new or expanding surgical epilepsy programs. Data regarding safety and efficacy are uncommon outside of high-volume, well-established centers, which may be less applicable to newer or low-volume centers. The objective of this study was to add to the sEEG outcomes in the literature from the perspective of a rapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…Five studies 24 - 28 ) were excluded considering that they did not mention the use of the ROSA Ⓡ device. Thus, in the final analysis, 15 studies 10 , 17 - 21 , 29 - 37 ) were included.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies 24 - 28 ) were excluded considering that they did not mention the use of the ROSA Ⓡ device. Thus, in the final analysis, 15 studies 10 , 17 - 21 , 29 - 37 ) were included.…”
Section: Resultsmentioning
confidence: 99%
“…Complications included intracranial haemorrhage in two, retained electrodes in three and two medical complications. 18 Méreaux et al also reported 49 consecutive SEEG cases showing death in one patient because of a delayed subdural haematoma and several other complications. Transient confusion and visuospatial symptoms were seen in two patients and electrode dysfunction occurred in six electrodes (1%), including one broken electrode.…”
Section: Discussionmentioning
confidence: 96%
“…recently described 152 SEEG cases with a major complication rate of 3.94% per procedure or 0.37% per electrode. Complications included intracranial haemorrhage in two, retained electrodes in three and two medical complications 18 . Méreaux et al .…”
Section: Discussionmentioning
confidence: 99%
“…They compare our results with those of Cardinale which included 500 patients. They also reference a report by Miller et al 4 of 152 patients using a standardized method and a meta-analysis with 2624 patients. 5 Comparison of these large series with a technical report of 9 patients during an initial period of learning is simply not justifiable.…”
mentioning
confidence: 97%